2022
DOI: 10.4103/iju.iju_186_22
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, observational study to assess the feasibility and safety of supine percutaneous nephrolithotomy under regional anesthesia for obese patients with a body mass index ≥30

Abstract: Introduction: Besides being a risk factor for urolithiasis, obesity is a challenge in the treatment of urolithiasis from the perspective of both the surgeon and the anesthetist. In this study, we tried to assess the feasibility and safety of supine percutaneous nephrolithotomy (PCNL) under regional anesthesia in obese patients with a body mass index (BMI) ≥30. Methods: This was a prospective observational study and included 51 obese patients (BMI ≥30 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Morsy et al, in his study on PCNL found good safety and feasibility of RA in 51 obese patients. 8 Gupta and Mahajan also reported suitability of RA in elderly, comorbid patients undergoing PCNL. 9 El-Husseiny et al, demonstrated that PCNL under SA or CSEA can be safely carried out in high-risk cases with ≥3 ASA class.…”
Section: Discussionmentioning
confidence: 95%
“…Morsy et al, in his study on PCNL found good safety and feasibility of RA in 51 obese patients. 8 Gupta and Mahajan also reported suitability of RA in elderly, comorbid patients undergoing PCNL. 9 El-Husseiny et al, demonstrated that PCNL under SA or CSEA can be safely carried out in high-risk cases with ≥3 ASA class.…”
Section: Discussionmentioning
confidence: 95%
“…Morsy et al [ 21 ] investigated the feasibility and safety of supine PCNL under RA in obese patients. They concluded that RA is feasible and safe in these patients with satisfactory stone-free rates and minimal postoperative pain.…”
Section: Discussionmentioning
confidence: 99%